Quantifying connectivity between mesophotic and shallow coral larvae in Okinawa Island, Japan: a quadruple nested high-resolution modeling study - Takeyasu, Kimika; Uchiyama, Yusuke; Mitarai, Satoshi (Frontiers in Marine Science, 2023)
Coral bleaching has recently been occurring extensively across the world’s oceans, primarily because of high water temperatures. Mesophotic corals that inhabit depths of approximately 30–150 m are expected to survive bleaching events and reseed shallow water corals afterward. In Okinawa, Japan, mesophotic coral ecosystems have been reported to serve as a refuge for preserving the genotypic diversity of bleaching-sensitive corals. The connectivity of larval populations among different habitats is a key element that determines the area to be conserved in desirable coral ecosystems. Because coral larvae are largely transported passively by ambient oceanic currents, particularly in the horizontal direction, numerical ocean circulation models greatly help to quantify connectivity with detailed spatiotemporal network structures. The present study aimed to quantify the short-distance connectivity of shallow and mesophotic coral larvae in reef areas on the northwest coast of Okinawa Island. To this end, a quadruple nested high-resolution synoptic ocean model at a lateral spatial grid resolution of 50 m was developed, which was capable of realizing detailed coastal currents influenced by complex nearshore topography, and coupled with an offline 3-D Lagrangian particle-tracking model. After validating the developed model, short-distance horizontal coral connectivity across reef areas on the northwest coast was successfully evaluated. The alongshore lateral connectivity had apparent asymmetry caused by depth-dependent horizontal currents, whereas the larvae spawned at shallow and mesophotic depths were reachable to each other. Such across-depth larval dispersal was attributable to the mixed-layer depth in the spawning period, viz., the boreal spring, which approximately coincides with the boundary between shallow and mesophotic coral, leading to the intensive vertical exchange of virtual larvae.